#TITLE_ALTERNATIVE# - TAUFAN ALFARISI (NIM : 12908011); Pembimbing : Dr. Eng.Hamzah Latief, MUHAMMAD
This study discribes a seabed morphological changes model around the nearshore breakwater due to sediment transport which is driven by nearshore waves and currents. The mild-slope equation is used in developing this model by using finite different method with staggered grid scheme. Pattern of wave transformation towards to the coast shows a superposition between incident and the reflected waves occurred in front of the breakwater, with high magnification reaching 7,1 cm about 60% of the wave height in similar places without breakwater. While the maximum wave height at behind of the breakwater decreases become 2,2 cm about 48,8% compared to the height reached without the presence of breakwater. Flow circulation pattern can be be illustrated well by the current model at around the coast. The results of the current model without breakwater with 0o angle of insidence shows that the longshore currents are not exist, while angle of insidence of 30o and 45o the longshore current are exist. On the other hand, on scenarios with breakwater shows apresence of eddies behind the breakwater. More greater of the incident wave angle make the flow pattern at behind the breakwater is shifted more to the obstructed area from the direction of the wave propagation due to the boost of longshore current. The seabed morphological change model gives a fairly good results with an error rate of 14.42% compared to Watanabe, et al model (1986) for cases with breakwater and perpendicular angle of insidence to the shoreline. In general, the process of tombolo formation can be seen, which was caused by shallowing occurred behind the breakwater. More greater of the incident waveangle, the shallowing area increasingly shifted toward the obstructed area from the direction of wave propagation.